2018
DOI: 10.1002/ca.23073
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral plexus root thickening: Establishing normal root dimensions using magnetic resonance neurography

Abstract: Disorders affecting the lumbosacral plexus (LSP) can alter root diameter. Our aim was to determine normal LSP nerve root dimensions using magnetic resonance neurography (MRN). Eleven asymptomatic patients (ages: 18-53, mean: 34 years) underwent MRN of the LSP on a 3 T scanner with an 8-channel torso-PA coil. IDEAL T2-weighted images were acquired and nerve root dimensions were measured from the second lumbar (L2) to the first sacral (S1) vertebrae on the coronal plane, 5 mm from the dorsal root ganglion (DRG).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The outcome of this study revealed that the LSP thickness increases by moving downward towed the sacrum as previously reported (14,16,17). The only study that contradicts the concept of gradual increase in LSP thickness was conducted by IZCI et al who reported that L1 is the thinnest root of the LSP (4.1 mm) and L4 is the thickest (5.5 mm) root of the LSP.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The outcome of this study revealed that the LSP thickness increases by moving downward towed the sacrum as previously reported (14,16,17). The only study that contradicts the concept of gradual increase in LSP thickness was conducted by IZCI et al who reported that L1 is the thinnest root of the LSP (4.1 mm) and L4 is the thickest (5.5 mm) root of the LSP.…”
Section: Discussionsupporting
confidence: 78%
“…The exact dimensions of human LSP thickness are varied in the literature. The clinical importance of morphometric data on LSP thickness has been emphasized by many studies (2,5,(14)(15)(16)(17). In this retrospective study, the thickness of LSP showed a gradual increase known as cephalo-caudal pattern from L1 to S1 (Table 1).…”
Section: Discussionmentioning
confidence: 76%
“…Despite the fact that MRI can be utilized for three-dimensional (3D) reconstruction of nerve tissues and ultrasound can be used for panoramic imaging of nerve tissues at present, they have the following limitations: 1. The boundary between the 3D neural imaging and surrounding tissue is blurred ( Kim et al, 2007 ; Chaves et al, 2018 ; van Rosmalen et al, 2021 ). 2.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most of da Vinci's work was unpublished, and thus, his brilliant records were not appreciated in the scientific literature of his day [2]. However, today, his accomplishments in neuroanatomy continue to be recognized [4,5]. …”
mentioning
confidence: 99%